Earth story - David, Sington (Australia : BBC Learning, 1999)
This program reveal the secret of the creation of the earth, the nature and its evolution
episode 1 The time travellers - episode 2 The deep - episode 3 Ring of fire - episode 4 Journey to the centre of the Earth - episode 5 The roof of the world - episode 6 The big freeze - episode 7 The living earth - episode 8 A world apart
Host: Aubrey Manning
Keywords: Earth sciences; Historical geology